A failed success: the Barlinnie Special Unit. Issue 1 (14th August 2020) - Wilson, David; Brookes, Michael
Abstract : Purpose: This paper aims to explore the reasons for and the subsequent longer-term impact of the closure of the Barlinnie Special Unit (BSU). Design/methodology/approach: The paper is both descriptive, providing an overview of the work of the BSU, and conceptual in that it argues that the limits of "prisoner rehabilitation" are observed in the closure of the BSU, which sounds a warning for other penal therapeutic communities and what it means to operate effectively. Findings: The BSU which assisted long-term, difficult and violent prisoners moderate their prison behaviour and then to live non-offending lives, lost the confidence of government ministers and officials, as well as senior prison managers and, seemingly, the public, so closed after being in operation for 21 years. The impact of this has been that the Scottish Prison Service has not introduced, or attempted to introduce, a similar regime for managing and treating violent and disruptive prisoners. Practical implications: There are important lessons to be learned from the BSU experience for all who manage and work in specialist, prison therapeutic units or within prison therapeutic regimes. This includes balancing the therapeutic elements of the regime, which may involve engaging in practices which are outside the norm for custodial establishments, with those establishments' security and operational requirements, so as to not to create a disconnect between addressing offending behaviour and maintaining expected standards of wider prison conduct. Originality/value: While there have been previous evaluations of the BSU, the longer-term impact has neither been previously considered and nor has the unit's closure been considered from a penal philosophical perspective.